2014
DOI: 10.1063/1.4866857
|View full text |Cite
|
Sign up to set email alerts
|

1-nm-thick graphene tri-layer as the ultimate copper diffusion barrier

Abstract: Articles you may be interested inEffect of interfacial interactions on the thermal conductivity and interfacial thermal conductance in tungsten-graphene layered structure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 45 publications
1
57
0
Order By: Relevance
“…Graphene has been demonstrated as an impermeable membrane for He 491 and both materials have been demonstrated as H 2 O/O 2 barriers for preventing oxidation of polymers and metals such as Cu and Ni. 492,493 Recently graphene (G) has also been demonstrated as a Cu diffusion barrier in Cu-G-Si structures annealed at temperatures up to 750…”
Section: 15mentioning
confidence: 99%
“…Graphene has been demonstrated as an impermeable membrane for He 491 and both materials have been demonstrated as H 2 O/O 2 barriers for preventing oxidation of polymers and metals such as Cu and Ni. 492,493 Recently graphene (G) has also been demonstrated as a Cu diffusion barrier in Cu-G-Si structures annealed at temperatures up to 750…”
Section: 15mentioning
confidence: 99%
“…The highly impermeable graphene has been demonstrated for impeding the migration of liquid, gas and chemical/biological molecules [12][13][14][15][16][17] . Recently, researchers used graphene layer for preventing the reaction and inter-diffusion at the interfaces of Al/Si, Cu/Si and Au/Ni [18][19][20] . These results indicate the possibility of introducing a graphene barrier into solid-state electrolyte devices, e.g., the controllable mass transport in electrochemical metallization memory cells.…”
mentioning
confidence: 99%
“…Wen Pu et al coated stainless steel (SUS304) substrates with graphene and reported a fivefold improvement in corrosion resistance from polarization tests carried out in 3.5 wt% saline environment (Pu et al 2015). Protection from oxidation was also reported at ambient and elevated temperatures (Chen et al 2011;Prasai et al 2012;Kirkland et al 2012;Nguyen et al 2014). It has been observed that the stability of graphene layer against oxidation is dependent on its nanostructure.…”
Section: Resultsmentioning
confidence: 99%